Characterization of a tetrameric proanthocyanidin in Stryphnodendron pulcherrimum and an overview on potential health benefits of condensed tannins via interaction with gut microbiota - Gomes, Paulo Wender P. (2023)
Stryphnodendron pulcherrimum is a plant found in the Brazilian Amazon and contains high content of catechin/(epi)catechin (flavan-3-ol) derivatives. The polymerization of this kind of flavan-3-ol generates condensed tannins, often associated to plant-based diets and gut microbiota. Thus, the discovery of condensed tannins from plants is a valuable approach once it enhances their availability from natural sources. Herein, we described a tetrameric condensed tannin (Molecular Mass 1,170 a.m.u.) tentatively identified for the first time in the barks from S. pulcherrimum. Condensed tannins-derived (flavan-3-ols units) are likely degraded in the gut, and their degradation products such as 3-hydroxyphenylacetic acid (OPAC), 3,4-dihydroxyphenylacetic acid (DHAA), 3-(3,4-dihydroxyphenyl)-propionic acid (DHPA), and 5-(3′,4′-dihydroxyphenyl)-γ-valerolactone (DHPV) could present benefits to gut microbiome metabolism. Therefore, this observational study represents a new insight into S. pulcherrimum, its molecules, and their potential benefits to avoid different diseases and gut well-functional.